2019
DOI: 10.1098/rsbl.2019.0747
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees use tree species with a resonant timbre for accumulative stone throwing

Abstract: Animals use tools for communication relatively rarely compared to tool use for extractive foraging. We investigated the tool-use behaviour accumulative stone throwing (AST) in wild chimpanzees, who regularly throw rocks at trees, producing impact sounds and resulting in the aggregations of rocks. The function of AST remains unknown but appears to be communication-related. We conducted field experiments to test whether impact sounds produced by throwing rocks at trees varied according to the tree's properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Although most research effort has focused of material cultures, there is no theoretical reason to believe that social effects would operate in starkly different ways with vocal and communicative behaviour. Great ape vocal research in the wild is inherently difficult and time intensive, but evidence for local traditions in sound communication 66 69 and call cultures 46 , 60 , 61 , 70 is steadily accumulating across great ape genera, even if great ape behavioural richness is eroding with human impact, and multiple local traditions should be assumed already extinct 71 , 72 .…”
Section: Mainmentioning
confidence: 99%
“…Although most research effort has focused of material cultures, there is no theoretical reason to believe that social effects would operate in starkly different ways with vocal and communicative behaviour. Great ape vocal research in the wild is inherently difficult and time intensive, but evidence for local traditions in sound communication 66 69 and call cultures 46 , 60 , 61 , 70 is steadily accumulating across great ape genera, even if great ape behavioural richness is eroding with human impact, and multiple local traditions should be assumed already extinct 71 , 72 .…”
Section: Mainmentioning
confidence: 99%
“…Related research has reported that chimpanzees at some study sites throw rocks at trees, referred to as accumulative stone‐throwing, or AST (Kühl et al, 2016). Kalan et al (2019) measured the spectral centroid, attack times, and damping coefficient of the sound produced when a rock impacts a tree. Impact sounds from AST trees were found to be more resonant than non‐AST trees, a quality well‐suited for propagating over long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Worthy of mention is such behavior among chimpanzees and Japanese macaques, who repeatedly visit specific locations where stones were used and/or cached while purposefully selecting and using previously used stones 95 , 96 . This was suggested to be an aspect of ritualized behavior among chimpanzees, including the recurring practice of selecting previously thrown stones and re-throwing these against the same tree 96 .While it is difficult to determine a clear reason behind the chimpanzee practice of throwing stones at specific trees and creating stone-cairns, a few possibilities have been suggested 96 98 .…”
Section: Discussionmentioning
confidence: 99%